Karnali Cable-Stayed Bridge: Development of Finite Element Model and Free Vibration Analysis - Shrestha, Bipin (Journal of the Institute of Engineering, 2014)
This paper describes an analytical investigation on Karnali cable stayed bridge across the Karnali River. The primary objective of the investigation is to develop a three dimensional finite element model capable of representing essential feature of the long span cable-stayed bridge. Various parametric studies on the simple cable-stayed bridge model are performed before the actual development of a complex three dimensional model. Deformed equilibrium configuration due to the dead load is calculated using the cable tension and applied dead loads. Importance of incorporating large displacement geometric nonlinearity during the dead load deformed equilibrium configuration is analyzed .Starting from the deformed equilibrium configuration; modal analysis of the bridge is carried out. Different observed modes are classified based on the dominant modal components. Comparisons of the global modal behavior using the two separate models utilizing different cable modeling techniques are made. Parametric study on effect of cable local vibration and the modeling of deck concrete of the composite deck on overall global modal characteristics is presented. DOI: http://dx.doi.org/10.3126/jie.v10i1.10873 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014 pp. 14-24